ASSESSING THE EFFECT OF PLACENTAL MALARIA ON NEONATAL BIRTH WEIGHTS IN UYO, NIGERIA - Johnson, Edidiong Asian; Ekuma, Agantem Emmanuel; Akinjogunla, Olajide Joseph; Udofia, Lydia Etuk; Abatai, Idongesit Isong (FUDMA JOURNAL OF SCIENCES, 2025)
Placental malaria (PM), caused by sequestration of Plasmodium falciparum-infected red blood cells in the placenta, disrupts nutrient and oxygen transfer to the fetus. It is strongly linked to low birthweight, intrauterine growth restriction, and increased neonatal mortality in malaria-endemic areas. This study assessed the prevalence of PM and its effect on birth weight among pregnant women in Uyo, Nigeria. A descriptive cross-sectional study was conducted among 405 pregnant women attending antenatal clinics in four health facilities, each from a different community in Uyo LGA. Data were collected using a structured interviewer-administered questionnaire. Venous blood samples were taken during pregnancy, and placental blood was collected after delivery. Data analysis was performed using SPSS version 25, with statistical significance set at p < 0.05. Respondents’ ages ranged from 16 to 46 years, with most aged 26–30 years. Malaria parasite prevalence was 25.9% (105/405). Prevalence was highest among women aged 16–20 years (80%) and lowest in those aged 41–46 years (14.2%), a statistically significant difference (p = 0.001). Malaria prevalence varied by trimester (p = 0.002), peaking in the first trimester (47.5%). Of the 106 women who delivered during the study, 18 (16.9%) had placental malaria. Newborns of malaria-positive mothers had lower birth weights (1.5–2.9 kg) compared to those of malaria-negative mothers (3.0–4.4 kg). The findings highlight a strong association between placental malaria especially early in pregnancy and low birth weight. Early diagnosis and intermittent preventive treatment are essential to reduce placental malaria and improve neonatal outcomes in endemic regions.
Keywords: Placental malaria; Birthweight; Pregnancy; Intermittent Preventive Treatment; Sulphadoxine Pyrimethamine; Uyo